Crystal structure of the kringle domain of human receptor tyrosine kinase‐like orphan receptor 1 (hROR1). Issue 5 (22nd April 2022) - Guarino, Salvatore R.; Di Bello, Antonella; Palamini, Martina; Capillo, Maria Chiara; Forneris, Federico
Abstract : The recombinant production, crystallization and high‐resolution X‐ray crystal structure of the isolated extracellular kringle domain of human receptor tyrosine kinase‐like orphan receptor 1 are reported, together with its comparison with previously solved three‐dimensional structures of other kringle domains and their complexes with antibody fragments. Abstract : Receptor tyrosine kinase‐like orphan receptors (RORs) are monotopic membrane proteins belonging to the receptor tyrosine kinase (RTK) family. RTKs play a role in the control of most basic cellular processes, including cell proliferation, differentiation, migration and metabolism. New emerging roles for RORs in cancer progression have recently been proposed: RORs have been shown to be overexpressed in various malignancies but not in normal tissues, and moreover an abnormal expression level of RORs on the cellular surface is correlated with high levels of cytotoxicity in primary cancer cells. Monoclonal antibodies against the extracellular part of RTKs might be of importance to prevent tumor cell growth: targeting extracellular kringle domain molecules induces the internalization of RORs and decreases cell toxicity. Here, the recombinant production and crystallization of the isolated KRD of ROR1 and its high‐resolution X‐ray crystal structure in a P 31 21 crystal form at 1.4 Å resolution are reported. The crystal structure is compared with previously solved three‐dimensional structures of kringle domains of human ROR1 and ROR2, their complexes with antibody fragments and structures of other kringle domains from homologous proteins.